2014
DOI: 10.4103/1305-7456.143628
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between International Normalized Ratio values and sufficiency of two different local hemostatic measures in anticoagulated patients

Abstract: Objectives:The management of patients receiving oral anticoagulant therapy (OAT) undergoing minor oral surgeries is controversial. This study was designed to evaluate the correlation between International Normalized Ratio (INR) values and the sufficiency of two different local hemostatic measures in controlling postextraction bleeding in anticoagulated patients.Materials and Methods:One hundred and sixty patients receiving Warfarin OAT were included in this study. Patients were selected so that 80 patients hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The chitosan dental dressing was mainly of use in these patients in achieving early hemostasis. Our study results are in accordance with Amer et al .,[15] who found a remarkable increase in the frequency of post-extraction bleeding in patients with INR values >2. However, regarding the adequacy of simple pressure pack in controlling post-extraction bleeding for patients with INR values of either ≤2 or >2, no significant results were noted.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The chitosan dental dressing was mainly of use in these patients in achieving early hemostasis. Our study results are in accordance with Amer et al .,[15] who found a remarkable increase in the frequency of post-extraction bleeding in patients with INR values >2. However, regarding the adequacy of simple pressure pack in controlling post-extraction bleeding for patients with INR values of either ≤2 or >2, no significant results were noted.…”
Section: Discussionsupporting
confidence: 93%
“…However, regarding the adequacy of simple pressure pack in controlling post-extraction bleeding for patients with INR values of either ≤2 or >2, no significant results were noted. [15]…”
Section: Discussionmentioning
confidence: 99%
“…sap in a 25 mg•mL 1 concentration was found to be a promising biomaterial, presenting significant hemorrhage action with therapeutic potential, to be used in the clinical treatment of local hemorrhage. Clinical trials in humans 39 could be used to confirm the hemostatic potential of the J. mollissima sap showed in this study, in addition to verifying whether smaller concentration could maintain the same hemostatic power and its mechanisms. Abbreviations: JM25, Jatropha mollissima 25 mg•mL 1 ; JM40, Jatropha mollissima 40 mg•mL 1 ; MO, Monsel's solution; SC, sodium chloride 0.9%.…”
Section: Discussionmentioning
confidence: 85%
“…In a study which was conducted with 160 patients, it was shown that ABS is effective for gingival bleedings (Amer et al 2014). In another study which was conducted by 25 patients who were undergone bronchoscopy procedure, ABS has successfully controlled the bleeding episodes of the cases (Uzun et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical efficacy of ABS in numerous systems had been demonstrated in the literature. For instance; ABS is very effective in the controlling of hemorrhages within the gingival tissue (Amer et al 2014), lung tissue (Uzun et al 2014), tooth extraction (Kazancıoğlu et al 2013; Tek et al 2014; Beyazit et al 2011), perineal tissue (Eyi et al 2013), oral mucosa tissue (Leblebisatan et al 2012), gastrointestinal tissue (Karaman et al 2012), thyroid tissue (Guler et al 2011), nasopharyngeal tissue (Iynen et al 2011; Yasar and Ozkul 2011), nasal tissue (Teker et al 2010), peritonsillary tissue (Teker et al 2009). Also, it has been reported that partial nephrectomy operation in human was performed without any complication with ABS (Huri et al 2010).…”
Section: Introductionmentioning
confidence: 99%